Impact of per-cycle changes in spatial and temporal pattern of dose and biokinetics in neuroblastoma patients receiving 177Lu-DOTATATE - Malcolm, J (2019)
Recently, there has been a growth in using post-treatment dosimetry after the first treatment cycle to plan the prescription for subsequent administrations to achieve an acceptable safe dose to kidneys and therapeutic dose to tumour. This level of personalisation recognises inter-patient variability in the uptake and clearance of 177Lu-DOTATATE by the kidneys and tumours. Increasingly, studies are showing additional variation in pharmacokinetics between cycles in an individual patient which may be particularly relevant in NETs cases in paediatric cases like NBL. The central goals for this work were to characterise variability in the spatial and temporal patterns of renal and tumour biokinetics and dose during a four cycle course of 177Lu-DOTATATE and investigate relationships between these variabilities and patient response.